Demography, baseline disease characteristics and treatment history of patients with psoriasis enrolled in a multicentre, prospective, disease‐based registry (PSOLAR)3. (16th July 2014) - Kimball, A.B.; Leonardi, C.; Stahle, M.; Gulliver, W.; Chevrier, M.; Fakharzadeh, S.; Goyal, K.; Calabro, S.; Langholff, W.; Menter, A.; the PSOLAR Steering Committee
Summary Background Psoriasis is associated with several comorbidities and behavioural risk factors. Objectives To evaluate demographic and disease characteristics in patients enrolled in the Psoriasis Longitudinal Assessment and Registry (PSOLAR). Methods PSOLAR is a global, prospective, longitudinal, disease‐based registry that includes a postmarketing commitment to evaluate safety in patients with psoriasis. Enrolled patients had to be receiving, or be eligible to receive, conventional systemic or biological agents. Demographic/disease characteristics, medical histories, lifestyle risk factors and previous treatments are collected at enrolment. Efficacy and safety data are collected every 6 months for 8 years, and data are extracted annually. Selected parameters are evaluated by age quartile using post hoc analyses. Results As of 23 August 2012, 11 900 patients were enrolled at 301 sites in North America, Europe and Latin America. Over half of the PSOLAR population (54·7%) is male, with a mean age of 48·6 years and mean body mass index of 30·9 kg m−2 at enrolment. Mean duration of disease at enrolment was 17·5 years, and mean Physician's Global Assessment score was 2·0. Psoriatic arthritis (35·5%) and cardiovascular diseases (38·2%) were highly prevalent. Diabetes mellitus type II was reported in 11·4% of patients. Depression and anxiety were noted in 14·7% and 11·1% of patients, respectively; 79·0% reported any alcohol use and 56·7% reported smoking or a history of smoking. The occurrence of most comorbidities, including cardiovascular disease and risk factors, increased with age. Conclusions In the PSOLAR population, multiple and age‐appropriate comorbidities are associated with psoriasis and may affect the selection of psoriasis treatments.